Dr. Ahmad Mahfuz and Dr. Hasnah win Best Article Writing Awards - Nor Salwana, Mohammad Idris (UMPSA, 2023)
PEKAN, 23 March 2023 - The lecturer of the Faculty of Industrial Science and Technology (FSTI), Universiti Malaysia Pahang (UMP), Dr. Ahmad Mahfuz Gazali emerged as the winner of the Best Article Writing Award for the Engineering, Science and Technology category while the lecturer of the Centre for Human Sciences (PSK), Dr. Hasnah Hussiin was named the winner in the category of Nationhood, Social Sciences and Humanities.